2020
DOI: 10.1001/jamapediatrics.2019.4878
|View full text |Cite
|
Sign up to set email alerts
|

Association of Opioid Prescribing Patterns With Prescription Opioid Overdose in Adolescents and Young Adults

Abstract: IMPORTANCE Safe opioid prescribing practices are critical to mitigate the risk of prescription opioid overdose in adolescents and young adults. However, studies that examine opioid prescribing patterns associated with prescription opioid overdose have mostly focused on older adults. The generalizability of these studies to adolescents and young adults is unclear.OBJECTIVE To identify opioid prescribing patterns associated with prescription opioid overdose in adolescents and young adults. DESIGN, SETTING, AND P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 36 publications
(104 reference statements)
7
89
0
1
Order By: Relevance
“…Over 500 children and adolescents died each year over a 17-year period due to opioid overdose [ 1 ]. An analysis of a nationwide claims database of 2.7 million patients under 21 years old found that higher amounts of opioids prescribed per day was associated with increased odds of overdose [ 22 ]. Thus, it is imperative that we make every effort to reduce opioid prescriptions in this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…Over 500 children and adolescents died each year over a 17-year period due to opioid overdose [ 1 ]. An analysis of a nationwide claims database of 2.7 million patients under 21 years old found that higher amounts of opioids prescribed per day was associated with increased odds of overdose [ 22 ]. Thus, it is imperative that we make every effort to reduce opioid prescriptions in this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…The overprescribing of opioids in the post-operative period is a widespread problem. It is well documented that the prescribing patterns of surgeons vary widely, particularly with respect to opioids intended for children and adults [ 23 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. It is estimated that between 42–72% of all post-operative opioid tablets are not consumed [ 22 , 35 ].…”
Section: In the Arms Of Morpheus Without Morphia; Mitigating The Umentioning
confidence: 99%
“…52 Additionally, research suggests that when practitioners prescribe opioids to youth, they should use the lowest effective daily dose, avoid prescribing opioids and benzodiazepines concurrently, and focus on prescribing short-acting opioids. 53 This study also highlights the need to prevent unintentional ingestion of substances in young children.…”
Section: Discussionmentioning
confidence: 82%